Case report: Detection of non-O1/non-O139 Vibrio cholerae in a patient with hepatic space-occupying lesions using metagenomic next-generation sequencing - Zhang, Wei; Xiao, Li; Shan, Xingxing; Dai, Bing; Tang, Chunyan; Xian, Jianchun; Yu, Yan (Frontiers in Medicine, 2024)
Introduction/background Vibrio cholerae is the causative agent of the human intestinal infectious disease cholera, which includes a variety of serogroups. However, there have been very few cases of hepatic space-occupying lesions associated with this infection. Currently, there are various methods for detecting this pathogen, including metagenomic sequencing, which enables quicker and more accurate identification. In this study, metagenomic sequencing is employed to accurately identify non-O1/O139 Vibrio cholerae infections by analyzing the genetic material present in clinical samples. Presentation of case A 75-year-old man presented with diarrhea and fever after consuming crabs. The initial treatment improved the diarrhea, but a liver abscess developed later. Magnetic resonance imaging (MRI) of the liver revealed a hepatic space-occupying lesion. Upon further investigation, a Gram-negative, rod-shaped bacterium was cultured from the patient’s liver puncture fluid, and Vibrio cholerae was detected in the same fluid using metagenomic next-generation sequencing (mNGS). The pathogen was confirmed to be non-O1/non-O139 Vibrio cholerae (NOVC) using polymerase chain reaction (PCR). Following treatment with piperacillin/tazobactam sodium and moxifloxacin, the patient’s body temperature returned to normal, the liver abscess improved significantly, and he was subsequently discharged from the hospital. Discussion This case study describes an elderly male patient with a hepatic space-occupying lesion. Multiple cultures of specimens failed to identify the underlying cause; however, advanced techniques such as mNGS and PCR confirmed an NOVC infection. This indicates that mNGS can serve as a valuable tool in diagnosing cases of unexplained liver infections. Conclusion The use of mNGS is significant for detecting and clinically diagnosing infectious pathogens in patients with unexplained space-occupying lesions.